Pendampingan Kemitraan Budidaya Bayam Merah pada Jama'ah Tani NU (JATANU) Desa Ngawun Parengan Tuban - Moh. Ihsan; M. Chairuddin (STAI Senori Tuban, 2025)
The purpose of this assistance is to increase the productivity and quality of the red spinach harvest of the farmer congregation, provide new knowledge and skills to the NU farmer congregation of Ngawun Village, Parengan District, Tuban Regency in managing red spinach plants intensively, and assist in marketing them by partnering with PT. Benih Citra Asia (PT. BCA). Using 2 methods, the first is to assist the farmer congregation by bringing together the farmer congregation with representatives from PT. BCA to then conduct socialization and an MoU between the NU farmer congregation and PT. BCA where PT. BCA will provide quality seeds and will buy the harvest of the Farmer Congregation at a good price according to the agreement. The second is to assist in the field starting from seeding, land preparation, planting, plant care, and handling pests and diseases to harvesting for 2.5 months. The results of this assistance are the diversification of the farmers’ crops, increased productivity, and quality of the farmers’ harvest directly purchased by the partner company in this case PT. BCA.